COVID-19, smart work, and collaborative space: A crisis-opportunity perspective - Richard Hu (Journal of Urban Management, 2020)
In this essay, I employ a crisis-opportunity perspective to approach the practice of smart work and the making of collaborative space in responding and adapting to COVID-19. These trends have been emerging at a faster pace in the recent decade, facilitated by a growing knowledge economy and information technological advancement. COVID-19 provides an extreme setting to test and trigger changes, and are likely to translate these emerging trends into a new normal in the way we work and the way we use space. This new normal, once established in the post-CVOID-19 world, will necessitate a new thinking about workplace management and space design to disrupt many norms rooted in an industrial age.
Keywords: 710; Canberra; Collaborative space; COVID-19; Smart work